Factors determining sports results in elite national volleyball teams between 2004 and 2016 - Mikolajec, K.; Nowak, B.; Banys, D.; Krzysztofik, M.; Skalski, D.T.; Markiel, A.; Maszczyk, A. (Biology of Sport, 2025)
The main objective of this study was to identify the game-related statistics determining the sports results in volleyball between 2004 and 2016. In the study, the matches of six men`s and six women`s national volleyball teams competing in the most prestigious international events were analysed. It should be emphasised that the data included in the analysis concerned the games played during the World Championship, Olympic Games, World Cup and the World Grand Champions Cup. The obtained results revealed that in the women`s group the variables number of successful attacks (p < 0.025) and number of blocking points (p < 0.044) were the fundamental factors determining success in volleyball at the elite level in the analysed period. Considering the main goal of the study, in men`s teams the number of blocking points (p < 0.007) and number of serve points (p < 0.008) were the main factors.